2009
DOI: 10.1097/pas.0b013e3181a755bd
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid (Cellcept and Myofortic) Induced Injury of the Upper GI Tract

Abstract: As noted by others (Parfitt JR, Jayakumar S, Driman DK. Am J Surg Pathol. 2008; 32:1367-1372), mycophenolate mofetil-associated injury of the upper GI tract, like that in the colon, is characterized by prominent apoptosis similar to that of mild or grade I graft-versus-host-disease injury. We offer apoptotic count guidelines, which we hope will facilitate recognition of mycophenolate mofetil-associated injury in the upper GI tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 31 publications
2
87
0
Order By: Relevance
“…This observation in our practice was paralleled by a growing body of literature on MPA-related histopathological findings [3,4,5,6]. MPA is an inhibitor of inosine-5′-monophosphate dehydrogenase and blocks the de novo purine synthesis required for DNA synthesis and cell division.…”
Section: Mpa-induced Colonopathymentioning
confidence: 76%
See 2 more Smart Citations
“…This observation in our practice was paralleled by a growing body of literature on MPA-related histopathological findings [3,4,5,6]. MPA is an inhibitor of inosine-5′-monophosphate dehydrogenase and blocks the de novo purine synthesis required for DNA synthesis and cell division.…”
Section: Mpa-induced Colonopathymentioning
confidence: 76%
“…These include points to be addressed from a basic research as well as a clinicopathological perspective. (1) Do the histopathological findings found in association with MPA treatment [3,4,6,10] correlate with the clinical symptoms, in particular diarrhea? The current concept is based on this assumption, but there are no data on the frequency of MPA-typical histopathological changes in patients not suffering from diarrhea.…”
Section: Mpa-induced Colonopathy: Perspectives and Unanswered Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Others have been more liberal in their assessment of ABs of the upper-gastrointestinal tract, including fragments of pyknotic basophilic material resembling a fried-egg in their AB counts. 3 In our experience, we have observed that individual pathologists define ABs differently, ranging from well-developed vacuolated cells to the presence of isolated basophilic granules. We typically consider both in our AB counts when evaluating small-bowel biopsies, and patients diagnosed with mild ACR using these features typically respond clinically and histologically to immunosuppression in an expected fashion.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the diagnosis of GvHD in the GI tract should not be based on histology alone but on a combination of clinical signs and symptoms, endoscopic findings, histopathology, and absence of infection by culture and histology [17]. Furthermore, apoptosis in any part of the GI tract can occur following various medications, including the immunosuppressive MMF, which can produce GVHD-like features, like dilated damaged crypts, edema in the lamina propria, increased crypt epithelial apoptosis, and patchy neutrophilic inflammation [26,27]. In our series, 46% of patients received CSA + MMF, and this treatment may have been a potential cause of misinterpretation of subtle histopathologic findings.…”
Section: Discussionmentioning
confidence: 99%